Effects of tadalafil treatment combined with physical activity in patients with low onset hypogonadism: results from a not-randomized single arm phase 2 study. (2nd July 2016) - Condorelli, Rosita A.; Calogero, Aldo E.; Di Mauro, Maurizio; Mongioì, Laura M.; Russo, Giorgio I.; Morgia, Giuseppe; La Vignera, Sandro
Abstract: Purpose : To investigate a possible relation between penile Doppler ultrasound examination (PDUE) parameters and efficacy of chronic therapy with tadalafil (TAD) combined with a protocol of aerobic physical activity (PA) in patients with late onset hypogonadism (LOH). Methods : The study evaluated 30 patients consecutively enrolled with LOH and erectile dysfunction which present contraindication to hormonal replacement therapy for concomitant prostate disease. These patients were subjected to a combined protocol with phosphodiesterase V selective inhibitors (TAD 5 mg daily) and aerobic PA. Results : After three months, we observed significant improvements in erectile function [IIEF-5, median (IQR) = 13.0 (7.0–18.0) versus 6.0 (5.0–6.75); p < 0.01] and of the main metabolic [homeostatic model assessment index, median (IQR) = 2.5 (1.62–3.37) versus 3.0 (2.0–3.75); p < 0.01; body mass index, median (IQR) = 27.0 (24.0–28.75) versus 27.5 (24.0–29.5)] and vascular parameters [peak systolic velocity, median (IQR) = 29.5 (24.25–31.0) versus 28.0 (23.0–24.25); acceleration time, median (IQR) = 114 (105.25–134.0) versus 115.0 (106.5–134.0)], assessed by PDUE. Conclusion : PA in association with phosphodiesterase V inhibitors could compensate the effects of hypogonadism on erectile function and facilitate the clinical response to these drugs even in the absence of adequate serum concentrations of total testosterone.